Perception of Nursing Managers Regarding the Implementation of Nurse Napping During Night Shifts - Zifriyanthi Minanda Putri; Lusi Andani; Esthika Ariany Maisa (Postgraduate, University of Mataram, 2025)
Napping is a short, intentional sleep that may reduce fatigue and improve alertness among night shift nurses. Sleep deprivation during 8- or 12-hour night shifts increases the risk of medical errors, health problems, and safety incidents. This study aimed to determine the perceptions of nursing managers regarding the implementation of nurse napping during night shifts at Hospital X in Padang City, West Sumatra. A quantitative descriptive design was used, involving 42 nursing managers selected through total sampling. Data were collected using a 15-item questionnaire assessing perceptions related to nurse napping and analyzed using univariate frequency distributions. The results showed that 57.1% of nursing managers had a positive perception of nurse napping. Most respondents strongly agreed that napping is an important need for nurses (59.5%) and that it can reduce medical errors and patient safety incidents (52.4%). These findings indicate general managerial support for nurse napping during night shifts. In conclusion, positive perceptions among nursing managers suggest that nurse napping may be considered as a strategy to enhance patient safety and promote occupational health and safety, and may serve as a basis for developing formal napping policies for night shift nurses.